The Role of Islamic Religious Education in Addressing the Impact of FoMO Among Adolescent Social Media Users - Hafni Sinaga, Laila; Bueraheng, Winarsari; Annatasya, Meiliza; Husna, Nurul (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
The phenomenon of Fear of Missing Out (FoMO) has become a common psychological issue among adolescent social media users. This condition is characterized by excessive anxiety when individuals feel left behind from others’ social activities in the digital space, potentially affecting their mental health and social behavior. This study aims to analyze the role of Islamic Religious Education in addressing the impact of FoMO among adolescents. The research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis is conducted using the Miles and Huberman model, while data validity is ensured through source and technique triangulation. The findings indicate that Islamic Religious Education plays a strategic role in fostering spiritual awareness, self-control, and values such as gratitude (shukr), contentment (qana’ah), and reliance on God (tawakkul), which help reduce FoMO tendencies among adolescents. Furthermore, the integration of Islamic values in learning enhances healthy and ethical digital literacy. Therefore, Islamic Religious Education can serve as both a preventive and curative solution in addressing the negative impacts of social media use.